2017
DOI: 10.1371/journal.pone.0169201
|View full text |Cite
|
Sign up to set email alerts
|

Locally Produced BDNF Promotes Sclerotic Change in Alveolar Bone after Nerve Injury

Abstract: Brain-derived neurotrophic factor (BDNF), which is released due to nerve injury, is known to promote the natural healing of injured nerves. It is often observed that damage of mandibular canal induces local sclerotic changes in alveolar bone. We reported that peripheral nerve injury promotes the local production of BDNF; therefore, it was possible to hypothesize that peripheral nerve injury affects sclerotic changes in the alveolar bone. This study aimed to evaluate the effect of BDNF on osteogenesis using in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 32 publications
2
32
1
Order By: Relevance
“…However, after 7 d BDNF did not increase the number of hMSCs. This corresponds with the result of Ida-Yonemochi et al (2017) who did not detect an increase in proliferation in MC3T3-E1 cells after 7 d [ 40 ]. In contrast, Cai et al (2010) showed that osteoblast proliferation increased after 6 d in a co-culture system of BDNF-producing Schwann cells and osteoblasts [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, after 7 d BDNF did not increase the number of hMSCs. This corresponds with the result of Ida-Yonemochi et al (2017) who did not detect an increase in proliferation in MC3T3-E1 cells after 7 d [ 40 ]. In contrast, Cai et al (2010) showed that osteoblast proliferation increased after 6 d in a co-culture system of BDNF-producing Schwann cells and osteoblasts [ 41 ].…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it was shown that BDNF is involved in fracture healing since it was detected in fracture gap tissue but not during physiological bone remodeling [ 12 ]. Moreover, BDNF significantly increased new bone formation after applying BDNF to mandibular osteotomies of rats [ 13 ]. Therefore, BDNF appears as potential drug suitable to be incorporated in CPCs and to stimulate bone formation during fracture healing in osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al verified the positive effect of 100 ng/mL BDNF on proliferation of human MSC [ 27 ]. In the murine osteoblast cell line MC3T3 proliferation was not enhanced by using 80 ng/mL of BDNF [ 19 ]. Thus, the appropriate concentration of BDNF for stimulation of proliferation is controversially discussed, and might be impaired by species and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of BDNF to monocyte cultures during differentiation into osteoclasts did neither impair the osteoclastogenesis nor the activity of osteoclasts if they were harvested from healthy donors [ 16 , 17 ]. In non-tumorigenic animal models, e.g., in murine and rat fracture models, the application of BDNF revealed enhanced bone formation and fracture healing [ 18 , 19 ]. The positive effect of BDNF on fracture healing was also determined when BDNF was released from a bone substitute material [ 18 ].…”
Section: Introductionmentioning
confidence: 99%